ANALISIS PENGARUH KURS RUPIAH DAN PAJAK PENGHASILAN TERHADAP PENANAMAN MODAL ASING DI PROVINSI KALIMANTAN BARAT - B21112023, Suharminto (Jurnal Curvanomic, 2016)
Foreign Direct Investment is a direct investment that provides many benefits to Indonesia including the entry of new capital for development, increase foreign exchange, the establishment of new companies that can provide technology transfer and operational management as well as provide employment. This research is motivated by the tendency of foreign direct investment continues to increase in the province of West Kalimantan in the period 2009-2013 year, as for the issues discussed were the factors that affect foreign direct investment in the province of West Kalimantan. The purpose of this study was to examine and analyze the effect of the Rupiah exchange rate, income taxes and the inflation rate towards foreign direct investment in the Province of West Kalimantan. The results showed that the Rupiah exchange rate had positive and significance effect on foreign direct investment while income tax and inflation rate had negative and significance effect on foreign direct investment. Simultaneously the Rupiah exchange rate, income tax and the inflation rateÂ  significantly influence foreign direct investment so it can be concluded that the higher the value of the Rupiah exchange rate would increase the amount of foreign direct investment whereas the higher income tax rate and the inflation rate will lead to a decrease in the amount of foreign direct investment. Keywords : Foreign Direct Investment,Â  Rupiah Exchange Rate, Income tax, Inflation Rate.